High efficiency THIPWM three-phase inverter for grid connected system - Younis M.A.A.; Rahim N.A.; Mekhilef S. (2023)
This paper presents a grid connected system. Three phase DC-AC inverters used to convert the regulated DC power to AC power suitable for grid connection. Third harmonic injection PWM (THIPWM) was employed to reduce the total harmonic distortion and for maximum use of the voltage source. DSP was used to generate the accurate THIPWM for grid connection, by synchronizing the inverter voltage with the grid voltage. The application of THIPWM to parallel connected inverter reduces the total harmonic distortion and increases efficiency of the inverter. Experimental results validate the developed model and the proposed system. 2010 IEEE.